Old cortex, new contexts: re-purposing spatial perception for social cognition - Parkinson, Carolyn; Wheatley, Thalia (Frontiers in Human Neuroscience, 2013)
Much of everyday mental life involves information that we cannot currently perceive directly, from contemplating the strengths of friendships to reasoning about the contents of other minds. Despite their primacy to everyday human functioning, and in particular, to human sociality, the mechanisms that support abstract thought are poorly understood. An explanatory framework that has gained traction recently in cognitive neuroscience is exaptation, or the re-purposing of evolutionarily old circuitry to carry out new functions. We argue for the utility of applying this concept to social cognition. Convergent behavioral and neuroscientific evidence suggests that humans co-opt mechanisms originally devoted to spatial perception for more abstract domains of cognition (e.g., temporal reasoning). Preliminary evidence suggests that some aspects of social cognition also involve the exaptation of substrates originally evolved for processing physical space. We discuss the potential for future work to test more directly if cortical substrates for spatial processing were exapted for social cognition, and in so doing, to improve our understanding of how humans evolved mechanisms for navigating an exceptionally complex social world.